Perkembangan Standar Akuntansi Keuangan Di Indonesia Ditinjau Dari Filsafat Ilmu - Hariyati hariyati (AKRUAL: JURNAL AKUNTANSI, 2011)
AbstractStandards of financial accounting is needed in the business community and the market economy system. Philosophically, the Financial Accounting Standards prepared for use (1) as a means of seeking truth from all the phenomena that exist, (2) to maintain, support and fight or stand neutral on the outlook, (3) to provide an understanding of the way of life, outlook on life and world view, (4) to give the doctrine of morals and ethics are useful in life, (5) to be a source of inspiration and guidance for life in various aspects of life itself, such as economics, politics, law and so on. Development of Accounting Standards in Indonesia can be divided into 3 (three) periods, namely (1) The period before the birth of the PAI, (2) Period of PAI to IFRSs and (3) Period of IFRS Convergence. The development of accounting standards from the period to the next because of a paradigm shift that occurred in that day. Interpretive very close to the development of accounting standards in Indonesia.Berkembangnya capital markets and money markets as well as with the inclusion of diera globalization, diverse accounting standards applicable in foreign countries determined to hold a convergence to IFRS. DSAK-IAI has set year 2012 as a milestone in the convergence of IFRS. In accordance with the objectives, functions, and characteristics of an accounting standard, IAS / IFRS will continue to evolve into increasingly complex and comprehensive in accordance with the spirit of the age and the phenomena that occur at this time.